Understanding The Concept of Zuhud in Fashion Trends in The Young Generation of Muslim Women - Abdullah, Mulyana (UIN Maulana Malik Ibrahim Malang, 2024)
For women, the beauty of their attire, including the hijab, holds significant meaning for their appearance and honor. Over time, social dynamics seem to